In vitro and In vivo Evaluation of Losartan Potassium Matrix Tablets Containing Poly(ethylene oxides) - Sasidhar, R.L.C.; Vidyadhara, S.; Nagaraju, R. (Asian Journal of Chemistry, 2011)
In the present investigation controlled release formulations of losartan potassium were formulated using poly(ethylene oxides) as release rate controlling polymer. Different excipients like ethyl cellulose, di calcium phosphate and starch 1500 were used in the preparation of matrix tablets and evaluated for their influence on controlled drug release. The matrix tablets were prepared by direct compression process and evaluated for hardness, weight variation, friability, swelling index and for in vitro release of the drug. Biopharmaceutical evaluation of satisfactory formulations were also carried out and parameters like Cmax, tmax, AUC0-t and AUMC0- t were determined. The studies were conducted on Newzealand rabbits. All the physical characteristics evaluated for the tablets were found to be within the acceptable limits. Higher polymeric content of poly(ethylene oxide) in the matrix tablets decreased the release rate of drug. At lower polymeric level the rate and extent of drug release was elevated. On the other hand the excipients like dibasic calcium phosphate, starch 1500 and ethyl cellulose have significantly retarded the release rate of losartan potassium. In vivo pharmacokinetic study proves that the losartan potassium from test tablets show prolonged release and may be able to sustain the therapeutic effect which can be further proved by pharmacodynamic study.